2022
DOI: 10.3390/foods11213324
|View full text |Cite
|
Sign up to set email alerts
|

Food Security in China: A Brief View of Rice Production in Recent 20 Years

Abstract: Rice production affects the food security and socioeconomic status of over half the world’s population. Rice-producing countries, however, are facing population growth, reduction in rice planting area, and global change. Understanding the trends of rice production and major determinants is key to regulating rice production. We thus analyzed the trends of rice production and related determinants in China from 2001 to 2021, revealing that the annual rice production (TRP) has risen steadily (r = 0.929, p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Ketika hasil panen melimpah, maka suatu daerah akan mampu memenuhi kebutuhan pangan penduduknya, yaitu kebutuhan beras (Kartiasih & Setiawan, 2019). Sesuai dengan Tang et al (2022) bahwa produksi beras berdampak pada ketahanan pangan, ketersediaan produksi padi dalam jumlah yang cukup dapat mengurangi risiko kelaparan dan kekurangan pangan.…”
Section: Analisis Inferensiaunclassified
“…Ketika hasil panen melimpah, maka suatu daerah akan mampu memenuhi kebutuhan pangan penduduknya, yaitu kebutuhan beras (Kartiasih & Setiawan, 2019). Sesuai dengan Tang et al (2022) bahwa produksi beras berdampak pada ketahanan pangan, ketersediaan produksi padi dalam jumlah yang cukup dapat mengurangi risiko kelaparan dan kekurangan pangan.…”
Section: Analisis Inferensiaunclassified
“…In China, rice accounts for almost 30% of global production and 28% of global consumption [ 22 ]. The study found that more than 50% of the global population relies on rice [ 23 ] to meet their dietary needs, and its production plays an important role in shaping the environmental profile of agricultural systems [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The examination extensively examines China as a prominent case study. By examining the spatial factors affecting rice output, we not only fulfil the critical requirement for well-informed decision-making in agriculture but also provide valuable contributions to sustainable food production and global food security [7].…”
Section: Introductionmentioning
confidence: 99%